Promotion of Environmental Culture: Diagnosis and Proposal for Intervention in an Educational Institution - Navarrete , Alexander; Valencia , Tamara (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Introduction: Environmental pollution in Ecuador constituted a critical problem, affecting both the quality of life of the population and the balance of ecosystems. Factors such as industrial activity, intensive agriculture and mining caused damage to soil, air and water. These problems had a direct impact on the health and academic performance of students, such as in the Ana Paez Educational Unit, located in Latacunga. Despite some efforts to care for the environment, the lack of genuine commitment and discontinuity of the initiatives limited their results. Development: The article showed that environmental education represented a key tool to address this problem in the institution. An educational campaign, called “SIC for nature”, was proposed, focused on raising awareness and involving students, teachers and parents in the conservation of green spaces. The campaign included strategies such as workshops, talks and ecological competitions, as well as the use of technological tools to promote sustainable habits. In addition, a diagnosis of existing practices made it possible to identify weaknesses and orient actions towards the specific needs of the educational community. Conclusions: The campaign designed in the Ana Paez Educational Unit highlighted the importance of encouraging the active participation of the educational community to generate a cultural change towards sustainability. The innovative strategies allowed not only to raise awareness among students, but also to provide them with practical tools to face environmental challenges. Finally, this proposal had the potential to be replicated in other educational institutions, strengthening an environmentally conscious culture and ensuring the preservation of the natural environment for future generations